Barriers to infection prevention and control practice among Amhara region teaching hospitals in Ethiopia: Qualitative study - Yallew, Walelegn Worku; Kumie, Abera; Yehuala, Feleke Moges (International Journal of Infection Control, 2019)
Healthcare workers have good perception towards infection prevention, but there has been a poor practice towards it. Therefore, the aim of this study was to explore barriers to practice of infection prevention and control practice in teaching hospitals in Amhara region. A phenomenological approach used to explore the lived experience of healthcare workers and management staffs towards infection prevention practice and control. The data was collected from ten in-depth interviews and 23 focus group discussion participants, by face to face interview using open ended interview performed in safe and quiet places. Data was managed using OpenCode software version 4.03 and contents were analyzed thematically. Totally ten different barriers were identified, such as availability of facilities, shortage of material supply, lack of maintenance of facilities and equipment, high patient flow, experience, emergency situation, healthcare worker behaviour and healthcare worker’s information about infection prevention, low awareness of patients and visitors and overflow of families and visitors to the hospital. For effective infection prevention practice implementation, barriers should be considered via identifying specific organizational, healthcare worker, patients and visitors as targets.